Accounting quality in private firms during the transition towards international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska (Accounting in Europe)
We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.  Full Article  Figures & data References  Citations Metrics  Reprints & Permissions  PDF Abstract We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.
Keywords: private firms; accounting quality; development of accounting standards; IFRS-like standards; Slovenia

Stackelberg Competition among Intermediaries in a Differentiated Duopoly with Product Innovation - Manegold, Jochen
On an intermediate goods market we consider vertical and horizontal product differentiation and analyze the impact of simultaneous competition for resources and the demand of customers on the market outcome. Asymmetries between intermediaries may arise due to distinct product qualities as well as by reasons of different production technologies. The intermediaries compete on the output market by choosing production quantities sequentially and for the supplies of a monopolistic input supplier on the input market. It turns out that there exist differences in product quality and productivities such that an intermediary being the Stackelberg leader has no incentive to procure inputs, whereas in the role of the Stackelberg follower will participate in the market. Moreover, we find that given an intermediary is more competitive, his equilibrium output quantity is higher when being the leader than when being the follower. Interestingly, if the intermediary is less competitive and goods are complements, there may exist asymmetries such that an intermediary being in the position of the Stackelberg follower offers higher output quantities in equilibrium than when being in the position of the Stackelberg leader.
Keywords: Input Market; Product Quality; Quantity Competition; Stackelberg Competition; Product Innovation

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska (Review of Accounting Studies)
We examine whether the mandated introduction of International Financial Reporting Standards (IFRS) is associated with the propensity to access the public rather than private debt market and the cost of debt. We use a global sample of public bonds and private loans and find that mandatory IFRS adopters are more likely, post-IFRS, to issue bonds than to borrow privately. We also find that mandatory IFRS adopters pay lower bond yield spreads, but not lower loan spreads, after the mandate. These findings are consistent with debt providers responding positively to financial reporting of higher quality and comparability, but only when there is a greater reliance on publicly available financial statements than private communication. Lastly, we document that the observed debt market benefits are concentrated in countries with larger differences between domestic GAAP and IFRS and are present even for EU countries that did not experience concurrent financial reporting enforcement or other institutional reforms. Overall, our study documents positive economic consequences around the mandated IFRS adoption for corporate debt financing and, in particular, for bond financing.
Keywords: Accounting regulation; IFRS; Accounting quality; Public and private debt markets; Cost of debt

Improving the bond quality of copper wire bonds using a friction model approach - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (Electronic Components and Technology Conference (ECTC), 2014 IEEE 64th)
In order to increase mechanical strength, heat dissipation and ampacity and to decrease failure through fatigue fracture, wedge copper wire bonding is being introduced as a standard interconnection method for mass production. To achieve the same process stability when using copper wire instead of aluminum wire a profound understanding of the bonding process is needed. Due to the higher hardness of copper compared to aluminum wire it is more difficult to approach the surfaces of wire and substrate to a level where van der Waals forces are able to arise between atoms. Also, enough friction energy referred to the total contact area has to be generated to activate the surfaces. Therefore, a friction model is used to simulate the joining process. This model calculates the resulting energy of partial areas in the contact surface and provides information about the adhesion process of each area. The focus here is on the arising of micro joints in the contact area depending on the location in the contact and time. To validate the model, different touchdown forces are used to vary the initial contact areas of wire and substrate. Additionally, a piezoelectric tri-axial force sensor is built up to identify the known phases of pre-deforming, cleaning, adhering and diffusing for the real bonding process to map with the model. Test substrates as DBC and copper plate are used to show the different formations of a wedge bond connection due to hardness and reaction propensity. The experiments were done by using 500 $μ$m copper wire and a standard V-groove tool.
Keywords: adhesion; circuit reliability; deformation; diffusion; fatigue cracks; friction; interconnections; lead bonding; van der Waals forces; Cu; adhering process; adhesion process; ampacity improvement; bond quality improvement; cleaning process; diffusing process; fatigue fracture failure; friction energy; friction model; heat dissipation; mechanical strength; piezoelectric triaxial force sensor; predeforming process; size 500 mum; total contact area; van der Waals forces; wedge copper wire bonding; Bonding; Copper; Finite element analysis; Force; Friction; Substrates; Wires

Synthesis of lead-free piezoelectric powders by ultrasonic-assisted hydrothermal method and properties of sintered (K0.48Na0.52)NBO3 ceramics - Isobe, G.; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics, Ferroelectrics, and Frequency Control, IEEE Transactions on)
(K,Na)NbO3 ceramics have attracted much attention as lead-free piezoelectric materials with high piezoelectric properties. High-quality (K,Na)NbO3 ceramics can be sintered using KNbO3 and NaNbO3 powders synthesized by a hydrothermal method. In this study, to enhance the quality factor of the ceramics, high-power ultrasonic irradiation was employed during the hydrothermal method, which led to a reduction in the particle size of the resultant powders.
Keywords: Q-factor; ceramics; crystal growth from solution; particle size; piezoelectric materials; potassium compounds; powders; sintering; sodium compounds; ultrasonic effects; (K0.48Na0.52)NbO3; KNbO3 powders; NaNbO3 powders; high-power ultrasonic irradiation; lead-free piezoelectric materials; lead-free piezoelectric powders; particle size reduction; piezoelectric properties; quality factor; sintered (K0.48Na0.52)NbO3 ceramics; sintering; ultrasonic-assisted hydrothermal method; Acoustics; Ceramics; Lead; Piezoelectric materials; Powders; Radiation effects; Transducers

Low temperature fabrication of a ZnO nanoparticle thin-film transistor suitable for flexible electronics - Vidor, F.F.; Wirth, G.I.; Hilleringmann, Ulrich (Microelectronics Reliability)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Safety; Risk; Reliability and Quality; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

A friction based approach for modeling wire bonding - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (IMAPS 2013, 46th International Symposium on Microelectronics)
A model approach for wedge/wedge bonding copper wire is presented. The connection between wire and substrate is based on a variety of physical effects, but the dominant one is the friction based welding while applying ultrasound. Consequently, a friction model was used to investigate the welding process. This model is built up universal and can be used to describe the formation of micro welds in the time variant contact area between wire and substrate. Aim of the model is to identify the interactions between touchdown, bond normal force, ultrasonic power and bonding time. To do so, the contact area is discretized into partial areas where a Point Contact Model is applied. Based on this approach it is possible to simulate micro and macro slip inside the contact area between wire and substrate. The work done by friction force is a main criterion to define occurring micro joints which influence the subsequent welding.
Keywords: Wire bonding; friction modeling; wire bond quality; contact element modeling

External governance outcome and microfinance success - Uhde, André; Müller, Oliver (International Journal of Monetary Economics and Finance)
Employing a Hausman–Taylor instrument variable (HT–IV) estimator to data from 558 microfinance institutions (MFIs) in 80 developing countries for the period from 2002 to 2007, this paper provides empirical evidence for a positive impact of a country's external governance quality and outcome on local microbanks' economic success in terms of profitability and sustainability. Evidence as well suggests a negative relationship between external governance and the microbanks' social success measured by the depth of outreach. In this context, our analysis reveals that a country's political stability, governance effectiveness, regulatory quality and rule of law are significant key elements of external governance affecting the MFIs' functional performance. Moreover, results from sensitivity analyses indicate that the relationship between external governance quality and microfinance functional performance significantly depends on the microbanks' business concepts, their lending methodologies and sources of funding.
Keywords: microfinance; external governance; economic success; social success; developing countries; profitability; sustainability; microbanks; outreach; political stability; governance effectiveness; regulatory quality; rule of law; governance quality; lending methodologies; funding sources

Measuring the quality of banking supervision revisited - Assessments by German banks before and during the financial crisis - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Governance and Regulation)
This contribution presents and discusses main results of a new survey on the assessment of supervisory quality among German banks in 2010. In particular, it is analyzed if and how supervised banks’ perception of the quality of supervisory authorities and their instruments has changed due to the financial crisis starting in mid-2007. Subsequently, results from the recent survey are compared with findings provided by a former study carried out by the authors in 2006 (Paul, Stein and Uhde, 2008).
Keywords: banking supervision; quality; assessment; banking sector

Measuring the relationship between supervisory authorities and banks: An assessment of the German banking sector - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Risk Managment in Financial Institutions)
The successful implementation of a harmonised regulatory framework for the global banking system is still a long way off. This mainly results from (a) different traditions in banking regulation and supervision at the national level, (b) different national emphases on regulatory sub-goals such as efficiency or the protection and promotion of national financial markets, and (c) different institutional settings and conditions. In this context, studies on the banking industry's assessment of supervisory processes and instruments highlight how effectively and efficiently individual nation states are implementing international frameworks such as Basel II and the Capital Requirements Directive for Europe. In November 2005, the German Government commissioned an evaluation of the supervisory processes and instruments of the country's banking authorities, BaFin and Bundesbank. The study aimed to determine the options for further optimising supervision, reducing regulatory burden and bureaucracy, and otherwise restricting supervision. This paper presents the most important findings from the survey, analyses significant differences in assessments given by various banking groups, empirically evaluates significant drivers of banks' overall satisfaction with banking supervision, and drafts proposals for improving banking regulation and supervision in Germany. Finally, aspects of further research are discussed.
Keywords: banking supervision; quality; assessment; banking sector

Social Work and the Quality of Life Politics - A Critical Assessment - Landhäußer, Sandra; Ziegler, Holger (Social Work & Society)
The feature of this paper is a critical assessment of the current discourses about quality of life (QoL) and their implications for Social Work. At first it pictures some major historical backgrounds of the discussion on the improvement of life quality as an aim of societal development. In particular three crucial shifts in the politics of QoL - its 'individualisation', its 'informalisation' and its 'culturalisation' - and their implications for Social Work are critically examined theoretically and empirically referring to the results of an own community-study. The paper concludes with an alternative suggestion reflecting the idea of an 'autonomy-based' approach of democratic equality.
Keywords: Critical; quality; Social